Türkçe ve edebiyat öğretmenlerinin ölçme ve değerlendirme araçları hakkında bilgi düzeyleri - (:unkn) unknown (My University, 2013)
Bu araştırmada Türkçe öğretmenleri ile Türk dili ve edebiyatı öğretmenlerinin öğretim sürecinde kullanmaları gereken ölçme-değerlendirme araç ve yöntemleri hakkında bilgi sahibi olup olmadıkları ve bu araçları kullanma düzeyleri sorgulanmıştır. Bu doğrultuda açık uçlu 10 soruluk anket Türkçe ve edebiyat öğretmenlerinden oluşan 53 kişiye uygulanmıştır. Tarama modelinde olan bu araştırmanın sonucunda her iki branşın öğretmenlerinin de ölçme ve değerlendirme yöntemleri hakkındaki bilgi ve kullanım düzeylerinin düşük olduğu tespit edilmiştir. Elde edilen bulgular ışığında bu düzeyin yükseltilmesi adına alana özgü ölçme-değerlendirme kılavuz kitaplarının hazırlanması önerisinde bulunulmuştur.

In this study, it is observed that whether the Turkish language and literature teachers and the Turkish lecture teachers have enough information about the tools and the methods of assessment that they need to use in the educational process and also the level of use of this information. In this perspective, in order to identify the teachers level of knowledge about this issue, an open-ended 10-item questionnaire is held. This questionare has been applied to 53 people composing of Turkish and literature teachers. As a result of this scanning model research, it has been identified that the level of information and usage of the measurement and evaluation tools and methods among the teachers of the both branches is at a very low level. According to results of this survey, to increase this level it is such suggested that some measurement and evalution books should be prepared .
Level of the information about turkish and literature teachers measurement and assessment materials
Keywords: Eğitim, Eğitim Araştırmaları